Acute Unilateral Total Visual Loss after Retrogasserian Phenol Injection for the Treatment of Trigeminal Neuralgia: A Case Report - Aydemir, Orhan; Yilmaz, Turgut; Onal, S. Ates; Celiker, Ulku; Erol, F. Serhat (Taylor & Francis Inc, 2006)
Phenol is a neurolytic agent that is widely used by percutaneous retrogasserian injection in the treatment of trigeminal neuralgia. We report a 78-year-old man who had acute unilateral total visual loss after retrogasserian phenol injection for the treatment of trigeminal neuralgia. The patient's visual acuity, eye movements and the pupillary defect did not improve in the affected eye even after mechanical decompression within 30 minutes and medical treatment, neither in the early period nor during the following two months. The visual loss in this patient seems to result from phenol neurotoxicity rather than mechanical compression of the intraorbital optic nerve. This case demonstrates that although percutaneous retrogasserian phenol injection is a relatively safe and noninvasive method of treatment for trigeminal neuralgia, severe complications may occur.
Keywords: Phenol injection; trigeminal neuralgia; visual loss